Electromagnetic wave shielding materials
A liquid crystal resin composition with balanced fibrous and granular conductive fillers addresses the issues of insufficient shielding and moldability, providing effective electromagnetic shielding and moldability for complex electronic components.
Patent Information
- Application Number
- JP2023517301
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-08-31
- Filing Date
- 2022-08-03
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2042-08-03
AI Technical Summary
Conventional liquid crystalline resin compositions lack sufficient electromagnetic shielding properties and have high melt viscosity, making them unsuitable for complex shape formation and moldability.
A liquid crystal resin composition containing a specific ratio of fibrous and granular conductive fillers, along with optional non-conductive fillers, within predetermined ranges, to achieve enhanced electromagnetic shielding and moldability.
The composition achieves electromagnetic shielding of 35 dB or more at 100 MHz with improved moldability, suitable for complex shapes and various electronic components.
Smart Images

Figure 0007612006000001 
Figure 0007612006000002 
Figure 0007612006000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an electromagnetic wave shielding member. [Background technology]
[0002] Liquid crystal resins, typified by liquid crystal polyester resins, have a good balance of excellent mechanical strength, heat resistance, chemical resistance, electrical properties, etc., and also have excellent dimensional stability, and are therefore widely used as high-performance engineering plastics. For example, Patent Document 1 discloses a liquid crystal polyester resin composition having excellent moldability, and also discloses that a molded product obtained by molding the liquid crystal polyester resin composition has excellent electromagnetic wave shielding properties and electrical insulation properties, and is useful as a member for electronic devices, etc. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2008-111010 A Summary of the Invention [Problem to be solved by the invention]
[0004] In recent years, with the transition from LTE to 5G, a significant improvement in signal transmission speed and signal accuracy is required for many products such as connectors, transmission boards, antennas, etc. As conductive materials such as connector materials are developed in relation to high-speed communications, the importance of thermoplastic conductive materials that can be given complex shapes as a noise countermeasure by forming electromagnetic wave shields is being highlighted.
[0005] As a candidate for the conductive material as described above, a liquid crystal resin composition can be mentioned. However, according to the study by the present inventors, conventional liquid crystal resin compositions do not have sufficient electromagnetic wave shielding properties, and also have high melt viscosity, so that molding processability is insufficient. The present invention has been made to solve the above problems, and its object is to provide an electromagnetic wave shielding member molded from a liquid crystal resin composition having excellent molding processability and having excellent electromagnetic wave shielding properties. [Means for solving the problem]
[0006] The present inventors have conducted extensive research to solve the above problems. As a result, they have found that the above problems can be solved by using an electromagnetic wave shielding member that is made of a molded body of a liquid crystal resin composition containing a liquid crystal resin, a fibrous conductive filler, and a granular conductive filler, in which the total content of the fibrous conductive filler and the granular conductive filler is within a predetermined range, the mass ratio of the content of the fibrous conductive filler to the content of the granular conductive filler is within a predetermined range, and the electromagnetic wave shielding property is within a predetermined range, and thus have completed the present invention. More specifically, the present invention provides the following.
[0007] (1) An electromagnetic wave shielding member comprising a molded product of a liquid crystalline resin composition containing (A) a liquid crystalline resin, (B) a fibrous conductive filler, and (C) a granular conductive filler, The total content of the (B) fibrous conductive filler and the (C) granular conductive filler is 15 to 60 mass %, the mass ratio of the content of the fibrous conductive filler (B) to the content of the granular conductive filler (C) is 0.30 to 22.0; The electromagnetic shielding member has an electromagnetic shielding property of 35 dB or more at a frequency of 100 MHz, as measured in accordance with the KEC method.
[0008] (2) the total content of the (B) fibrous conductive filler and the (C) granular conductive filler is 20 to 50 mass %, The electromagnetic shielding material according to (1), wherein the mass ratio of the content of the fibrous conductive filler (B) to the content of the particulate conductive filler (C) is 0.50 to 20.0.
[0009] (3) The (B) fibrous conductive filler is a carbon fiber, The electromagnetic shielding material according to (1) or (2), wherein the particulate conductive filler (C) is carbon black.
[0010] (4) The electromagnetic shielding material according to any one of (1) to (3), wherein the liquid crystalline resin composition further contains (D) a non-conductive filler.
[0011] (5) The electromagnetic shielding material according to any one of (1) to (4), wherein the content of the non-conductive filler (D) is 2 to 8 mass %.
[0012] (6) The electromagnetic shielding member according to (4) or (5), wherein the (D) non-conductive filler is at least one selected from the group consisting of talc, mica, glass flakes, silica, glass beads, glass balloons, potassium titanate whiskers, calcium silicate whiskers, milled glass fibers, and glass fibers.
[0013] (7) The electromagnetic shielding material according to any one of (4) to (6), wherein the non-conductive filler (D) is at least one selected from the group consisting of talc, mica, silica, and glass fiber. Effect of the Invention
[0014] According to the present invention, it is possible to provide an electromagnetic wave shielding member which is molded from a liquid crystalline resin composition having excellent moldability and has excellent electromagnetic wave shielding properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] Hereinafter, an embodiment of the present invention will be described, however, the present invention is not limited to the following embodiment.
[0016] <Electromagnetic wave shielding materials> The electromagnetic shielding member of the present invention comprises a molded product of a liquid crystalline resin composition containing (A) a liquid crystalline resin, (B) a fibrous conductive filler, and (C) a granular conductive filler, the total content of the (B) fibrous conductive filler and the (C) granular conductive filler is 15-60 mass%, the mass ratio of the content of the (B) fibrous conductive filler to the content of the (C) granular conductive filler is 0.30-22.0, and the electromagnetic shielding property at a frequency of 100 MHz measured in accordance with the KEC method is 35 dB or more. The electromagnetic shielding member of the present invention is molded from a liquid crystalline resin composition having excellent moldability and has excellent electromagnetic shielding property.
[0017] The electromagnetic shielding member according to the present invention has an electromagnetic shielding property of 35 dB or more at a frequency of 100 MHz, as measured in accordance with the KEC method, and is excellent in electromagnetic shielding property. The electromagnetic shielding property is preferably 37 dB or more, and more preferably 38 dB or more.
[0018] The electromagnetic wave shielding member of the present invention can be suitably used in applications requiring excellent electromagnetic wave shielding properties, and specifically, can be used in a wide range of applications, including various cases, gear cases, LED packages and LED lamp-related parts, connectors, relay cases, switches, variable capacitor cases, optical pickup lens holders, optical pickup slide bases, lamp reflectors, various terminal boards, transformers, printed wiring boards, liquid crystal panel frames, power modules and their housings, plastic magnets, semiconductors, liquid crystal display parts, lamp covers for projectors and the like, FDD carriages, FDD chassis, actuators, chassis and other HDD parts, computer-related parts, and other electric and electronic parts; VTR parts, television parts, iron parts, hair dryer parts, rice cooker parts, microwave oven parts, audio parts, audio equipment parts (e.g., audio, laser discs (registered trademark), compact discs, digital video discs, etc.), lighting parts, refrigerator parts, air conditioner parts, and other home and office electrical appliance parts; office computers, etc. It can be particularly suitably used for: pewter-related parts, telephone-related parts, facsimile-related parts, printer / copier-related parts such as print heads and transfer rolls, cleaning jigs, motor parts, microscope parts, binoculars parts, camera parts, watch parts, and other optical equipment / precision machinery-related parts; alternator terminals, alternator connectors, IC regulators, light dimmer potentiometer bases, motor core sealing materials, insulator parts, power seat gear housings, air conditioner thermostat bases, air conditioner panel switch boards, horn terminals, electrical component insulating plates, lamp housings, ignition device cases, air pressure sensors, fuse connectors, vehicle speed sensors, and other automobile / vehicle-related parts; computer housings, mobile phone housings, antenna cases for mobile phone base stations, chip antennas in the information and communications field, wireless LAN antennas, ETC (Electronic Torque Collection System) antennas, satellite communication antennas, and other information and communications-related parts.
[0019] [(A) Liquid crystal resin] The liquid crystal resin (A) used in the present invention refers to a melt-processable polymer having the property of being capable of forming an optically anisotropic molten phase. The property of the anisotropic molten phase can be confirmed by a conventional polarized light inspection method using crossed polarizers. More specifically, the anisotropic molten phase can be confirmed by observing a molten sample placed on a Leitz hot stage at a magnification of 40 times under a nitrogen atmosphere using a Leitz polarizing microscope. When the liquid crystal polymer applicable to the present invention is inspected between crossed polarizers, it usually transmits polarized light even in a molten stationary state, and is optically anisotropic.
[0020] The type of the liquid crystal resin (A) as described above is not particularly limited, and is preferably an aromatic polyester and / or an aromatic polyesteramide. Also, polyesters partially containing aromatic polyester and / or aromatic polyesteramide in the same molecular chain are included in the scope. As the liquid crystal resin (A), one having an inherent viscosity (IV) of preferably at least about 2.0 dl / g, more preferably 2.0 to 10.0 dl / g when dissolved in pentafluorophenol at a concentration of 0.1 mass% at 60°C is preferably used.
[0021] The aromatic polyester or aromatic polyesteramide as the (A) liquid crystalline resin applicable to the present invention is particularly preferably an aromatic polyester or aromatic polyesteramide having, as a constituent component, a constituent unit derived from at least one selected from the group consisting of aromatic hydroxycarboxylic acids and derivatives thereof.
[0022] More specifically, (1) A polyester mainly composed of structural units derived from at least one selected from the group consisting of aromatic hydroxycarboxylic acids and derivatives thereof; (2) A polyester mainly composed of (a) a structural unit derived from at least one selected from the group consisting of aromatic hydroxycarboxylic acids and derivatives thereof, and (b) a structural unit derived from at least one selected from the group consisting of aromatic dicarboxylic acids, alicyclic dicarboxylic acids, and derivatives thereof; (3) A polyester mainly composed of (a) a structural unit derived from at least one selected from the group consisting of aromatic hydroxycarboxylic acids and derivatives thereof, (b) a structural unit derived from at least one selected from the group consisting of aromatic dicarboxylic acids, alicyclic dicarboxylic acids, and derivatives thereof, and (c) a structural unit derived from at least one selected from the group consisting of aromatic diols, alicyclic diols, aliphatic diols, and derivatives thereof; (4) A polyesteramide mainly composed of (a) a structural unit derived from at least one selected from the group consisting of aromatic hydroxycarboxylic acids and derivatives thereof, (b) a structural unit derived from at least one selected from the group consisting of aromatic hydroxyamines, aromatic diamines, and derivatives thereof, and (c) a structural unit derived from at least one selected from the group consisting of aromatic dicarboxylic acids, alicyclic dicarboxylic acids, and derivatives thereof; (5) polyesteramides mainly consisting of (a) structural units derived from at least one selected from the group consisting of aromatic hydroxycarboxylic acids and their derivatives, (b) structural units derived from at least one selected from the group consisting of aromatic hydroxyamines, aromatic diamines and their derivatives, (c) structural units derived from at least one selected from the group consisting of aromatic dicarboxylic acids, alicyclic dicarboxylic acids and their derivatives, and (d) structural units derived from at least one selected from the group consisting of aromatic diols, alicyclic diols, aliphatic diols and their derivatives. If necessary, a molecular weight modifier may be used in combination with the above structural components.
[0023] Preferred examples of specific compounds constituting the (A) liquid crystal resin applicable to the present invention include aromatic hydroxycarboxylic acids such as 4-hydroxybenzoic acid and 6-hydroxy-2-naphthoic acid; aromatic diols such as 2,6-dihydroxynaphthalene, 1,4-dihydroxynaphthalene, 4,4'-dihydroxybiphenyl, hydroquinone, resorcin, a compound represented by the following general formula (I), and a compound represented by the following general formula (II); aromatic dicarboxylic acids such as 1,4-phenylenedicarboxylic acid, 1,3-phenylenedicarboxylic acid, 4,4'-diphenyldicarboxylic acid, 2,6-naphthalenedicarboxylic acid, and a compound represented by the following general formula (III); and aromatic amines such as p-aminophenol, p-phenylenediamine, and N-acetyl-p-aminophenol. [ka] (X: alkylene (C 1 ~C 4 ), alkylidene, -O-, -SO-, -SO 2 is a group selected from -, -S-, and -CO-. [ka] [ka] (Y:-(CH 2 ) n -(n=1 to 4) and -O(CH 2 ) n O-(n=1 to 4).
[0024] The liquid crystal resin (A) used in the present invention can be prepared by a known method using a direct polymerization method or an ester exchange method from the above-mentioned monomer compound (or a mixture of monomers). Usually, a melt polymerization method, a solution polymerization method, a slurry polymerization method, a solid-phase polymerization method, or a combination of two or more of these methods is used, and a melt polymerization method or a combination of a melt polymerization method and a solid-phase polymerization method is preferably used. The above-mentioned compounds having an ester forming ability may be used in the polymerization in their original form, or may be modified from a precursor to a derivative having an ester forming ability in a stage before polymerization. Various catalysts can be used in these polymerizations, and representative examples include metal salt catalysts such as potassium acetate, magnesium acetate, stannous acetate, tetrabutyl titanate, lead acetate, sodium acetate, antimony trioxide, and tris(2,4-pentanedionato)cobalt(III), and organic compound catalysts such as 1-methylimidazole and 4-dimethylaminopyridine. The amount of the catalyst used is generally about 0.001 to 1 mass% relative to the total mass of the monomers, and particularly about 0.01 to 0.2 mass% is preferable. If necessary, the molecular weight of the polymer produced by these polymerization methods can be increased by a solid-phase polymerization method in which the polymer is heated under reduced pressure or in an inert gas.
[0025] The melt viscosity of the liquid crystal resin (A) obtained by the above method is not particularly limited. In general, the melt viscosity at the molding temperature is 1000 s -1 Liquid crystal resins having a viscosity of 3 Pa s or more and 500 Pa s or less can be used. However, liquid crystal resins with a viscosity that is too high in itself are not preferred because they will significantly deteriorate the flowability. The liquid crystal resin (A) may be a mixture of two or more kinds of liquid crystal resins.
[0026] In the liquid crystal resin composition of the present invention, the content of the liquid crystal resin (A) is preferably 40 to 85 mass%, more preferably 50 to 80 mass%, and further more preferably 60.5 to 79.5 mass%. The content of the component (A) within the above range is preferable in terms of flowability, heat resistance, etc.
[0027] [(B) Fibrous conductive filler] The liquid crystal resin composition according to the present invention contains a fibrous conductive filler. The fibrous conductive filler may be used alone or in combination of two or more.
[0028] The average fiber length of the (B) fibrous conductive filler is not particularly limited, and may be, for example, 50 μm or more and 10 mm, 80 μm or more and 8 mm, or 100 μm or more and 7 mm, from the viewpoint of conductivity. In this specification, the average fiber length of the (B) fibrous conductive filler is determined by importing 10 stereomicroscope images of the fibrous conductive filler from a CCD camera into a PC, and measuring the fiber length of 100 fibrous conductive fillers for each stereomicroscope image, i.e., a total of 1000 fibrous conductive fillers, using an image processing method with an image measuring device. The average fiber length of the (B) fibrous conductive filler in the liquid crystal resin composition is measured by applying the above method to the fibrous conductive filler remaining after heating the liquid crystal resin composition at 500° C. for 4 hours to incinerate it.
[0029] The fiber diameter of the (B) fibrous conductive filler is not particularly limited, and may be, for example, 0.2 to 15 μm, 0.25 to 13 μm, or 0.3 to 11 μm from the viewpoint of electrical conductivity. In this specification, the fiber diameter of the (B) fibrous conductive filler is determined by observing the fibrous conductive filler with a scanning electron microscope and measuring the fiber diameter of 30 pieces of the fibrous conductive filler. The fiber diameter of the (B) fibrous conductive filler in the liquid crystal resin composition is measured by applying the above-mentioned method to the fibrous conductive filler remaining after heating the liquid crystal resin composition at 500° C. for 4 hours to incinerate it.
[0030] (B) Examples of the fibrous conductive filler include carbon fiber; conductive fibers such as metal fibers; and inorganic fibrous substances coated with a metal such as nickel or copper to impart conductivity. From the viewpoint of conductivity, carbon fiber is preferred.
[0031] Examples of carbon fibers include PAN-based carbon fibers made from polyacrylonitrile and pitch-based carbon fibers made from pitch.
[0032] Examples of metal fibers include fibers made of mild steel, stainless steel, steel and its alloys, copper, brass, aluminum and its alloys, titanium, lead, etc. These metal fibers have electrical conductivity, and if necessary, they can be coated with other metals to further impart electrical conductivity.
[0033] Examples of the inorganic fibrous material include glass fibers, milled glass fibers, asbestos fibers, silica fibers, silica-alumina fibers, zirconia fibers, boron nitride fibers, silicon nitride fibers, boron fibers, potassium titanate whiskers, calcium silicate whiskers (fibrous wollastonite), and the like.
[0034] [(C) Granular conductive filler] The liquid crystal resin composition according to the present invention contains a particulate conductive filler. The particulate conductive filler may be used alone or in combination of two or more.
[0035] The median diameter of the particulate conductive filler (C) is not particularly limited, and may be, for example, 10 nm to 50 μm, 15 nm to 20 μm, or 18 nm to 10 μm from the viewpoint of conductivity. In this specification, the median diameter refers to the volume-based median value measured by a laser diffraction / scattering particle size distribution measurement method.
[0036] (C) The granular conductive filler includes carbon black, granular metal powder (e.g., aluminum, iron, copper), granular conductive ceramics (e.g., zinc oxide, tin oxide, indium tin oxide), etc., and from the viewpoint of conductivity, carbon black is preferred. The carbon black is not particularly limited as long as it is a generally available carbon black used for resin coloring. Usually, carbon black contains lumps formed by agglomeration of primary particles, but unless it contains a significantly large amount of lumps having a size of 50 μm or more, many bumps (fine bumpy protrusions (fine unevenness) formed by agglomeration of carbon black) are unlikely to occur on the surface of the molded body obtained by molding the resin composition of the present invention. If the content of particles having a particle diameter of 50 μm or more is 20 ppm or less, the smoothness of the molded body surface is likely to be high. The preferred content is 5 ppm or less.
[0037] The total content of the (B) fibrous conductive filler and the (C) granular conductive filler in the liquid crystal resin composition of the present invention is 15 to 60 mass%, preferably 20 to 50 mass%, and more preferably 20.5 to 39.5 mass%. When the total content is 15 mass% or more, a molded product having improved electromagnetic wave shielding properties is easily obtained. When the total content is 60 mass% or less, the fluidity of the liquid crystal resin composition is easily improved, and a liquid crystal resin composition having excellent moldability is easily obtained.
[0038] The mass ratio of the content of the fibrous conductive filler (B) to the content of the granular conductive filler (C) is 0.30 to 22.0, preferably 0.40 to 21.0, and more preferably 0.50 to 20.0. When the mass ratio is 0.30 or more, the fluidity of the liquid crystalline resin composition is easily improved, and it is easy to obtain a liquid crystalline resin composition having excellent moldability and a molded article having improved electromagnetic wave shielding properties. When the mass ratio is 20.0 or less, it is easy to obtain a molded article having improved electromagnetic wave shielding properties.
[0039] [(D) Non-conductive filler] The liquid crystal resin composition according to the present invention may contain a non-conductive filler. The non-conductive filler may be used alone or in combination of two or more. (D) Examples of the non-conductive filler include a plate-like non-conductive filler, a granular non-conductive filler, and a fibrous non-conductive filler.
[0040] The median diameter of the plate-like non-conductive filler is not particularly limited, and may be, for example, 10 to 100 μm, 12 to 50 μm, or 14 to 30 μm. From the viewpoint of electromagnetic shielding properties, even if the electromagnetic shielding member according to the present invention is made of a molded body having a complex shape, it is preferable that the variation in volume resistivity, which is an index of conductivity, is small regardless of the thickness of the molded body. When the median diameter of the plate-like non-conductive filler is 10 to 100 μm, the thickness dependency of the conductivity of the molded body is easily reduced, and it is easy to obtain a molded body with small variation in volume resistivity regardless of the thickness. Examples of the plate-like non-conductive filler include talc, mica, and glass flakes.
[0041] The median diameter of the granular non-conductive filler is not particularly limited, and may be, for example, 0.3 to 50 μm, 0.4 to 25 μm, or 0.5 to 5.0 μm. When the median diameter of the granular non-conductive filler is 0.3 to 50 μm, the thickness dependency of the conductivity of the molded body is easily reduced, and it is easy to obtain a molded body with small fluctuations in volume resistivity regardless of the thickness. Examples of the granular non-conductive filler include silica, quartz powder, glass beads, glass balloons, glass powder, calcium silicate, aluminum silicate, kaolin, clay, diatomaceous earth, wollastonite and other silicates; iron oxide, titanium oxide, zinc oxide, alumina and other metal oxides; calcium carbonate, magnesium carbonate and other metal carbonates; calcium sulfate, barium sulfate and other metal sulfates; silicon carbide; silicon nitride; boron nitride and the like.
[0042] The average fiber length of the fibrous non-conductive filler is not particularly limited, and may be, for example, 50 μm or more and 10 mm, 80 μm or more and 7 mm, or 100 μm or more and 4 mm. When the average fiber length of the fibrous non-conductive filler is 50 μm or more and 10 mm, the thickness dependency of the conductivity of the molded body is easily reduced, and it is easy to obtain a molded body with small fluctuations in volume resistivity regardless of the thickness. The fiber diameter of the fibrous non-conductive filler is not particularly limited, and may be, for example, 0.2 to 15 μm, 0.25 to 13 μm, or 0.3 to 11 μm. When the fiber diameter of the fibrous non-conductive filler is 0.2 to 15 μm, the thickness dependency of the conductivity of the molded body is easily reduced, and it is easy to obtain a molded body with small fluctuations in volume resistivity regardless of the thickness. The average fiber length of the fibrous non-conductive filler and the fiber diameter of the fibrous non-conductive filler are each the average of the values measured in the same manner as described above for the (B) fibrous conductive filler. Examples of fibrous non-conductive fillers include inorganic fibrous materials such as glass fibers, milled glass fibers, asbestos fibers, silica fibers, silica-alumina fibers, zirconia fibers, boron nitride fibers, silicon nitride fibers, boron fibers, potassium titanate whiskers, and calcium silicate whiskers (fibrous wollastonite).
[0043] Since the thickness dependency of the electrical conductivity of the molded article is more easily reduced and a molded article having small variation in volume resistivity regardless of thickness is more easily obtained, the non-conductive filler (D) is preferably one or more selected from the group consisting of talc, mica, glass flakes, silica, glass beads, glass balloons, potassium titanate whiskers, calcium silicate whiskers, milled glass fiber, and glass fiber, and more preferably one or more selected from the group consisting of talc, mica, silica, and glass fiber.
[0044] The content of the non-conductive filler (D) in the liquid crystal resin composition of the present invention is preferably 2 to 8 mass%, more preferably 2.3 to 7.7 mass%, and even more preferably 2.5 to 7.5 mass%. When the content is 2 to 8 mass%, the fluidity of the liquid crystal resin composition is easily improved, and a liquid crystal resin composition having excellent moldability is easily obtained.
[0045] [Other ingredients] To the liquid crystal resin composition of the present invention, other polymers, other fillers, and known substances generally added to synthetic resins, i.e., stabilizers such as antioxidants and ultraviolet absorbers, antistatic agents, flame retardants, colorants such as dyes and pigments, lubricants, crystallization accelerators, crystal nucleating agents, release agents, and other components can be appropriately added depending on the required performance, within the range not impairing the effects of the present invention. The other components may be used alone or in combination of two or more.
[0046] The other polymers include, for example, epoxy group-containing copolymers. The other polymers may be used alone or in combination of two or more.
[0047] The other fillers refer to fillers other than the (B) fibrous conductive filler, the (C) granular conductive filler, and the (D) non-conductive filler, and examples thereof include conductive fillers other than the (B) component and the (C) component. The other fillers may be used alone or in combination of two or more. Examples of conductive fillers other than the (B) component and the (C) component include plate-shaped conductive fillers.
[0048] [Method for preparing liquid crystal resin composition] The method for preparing the liquid crystal resin composition of the present invention is not particularly limited. For example, the liquid crystal resin composition is prepared by blending the above-mentioned (A) to (C) components, optionally (D) component, and optionally at least one of other components, and melt-kneading the mixture using a single-screw or twin-screw extruder.
[0049] [Liquid crystal resin composition] The liquid crystalline resin composition of the present invention obtained as described above has a melt viscosity of preferably 180 Pa·sec or less, more preferably 145 Pa·sec or less, and even more preferably 140 Pa·sec or less, from the viewpoints of fluidity during melting and moldability. In this specification, the melt viscosity is defined as the viscosity at a cylinder temperature 10 to 20°C higher than the melting point of the liquid crystalline resin, a shear rate of 1000 sec -1The value obtained using a measurement method conforming to ISO 11443 under the above conditions is used. EXAMPLES
[0050] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0051] <Liquid crystal resin> Liquid crystal polyester amide resin (LCP1) After the following raw materials were charged into the polymerization vessel, the temperature of the reaction system was raised to 140°C and reacted at 140°C for 1 hour. Thereafter, the temperature was further raised to 340°C over 4.5 hours, and then the pressure was reduced to 10 Torr (i.e. 1330 Pa) over 15 minutes, and melt polymerization was carried out while distilling off acetic acid, excess acetic anhydride, and other low boiling points. After the stirring torque reached a predetermined value, nitrogen was introduced to change from a reduced pressure state to a normal pressure state and then to a pressurized state, the polymer was discharged from the bottom of the polymerization vessel, and the strands were pelletized to obtain pellets. The obtained pellets were heat-treated at 300°C for 2 hours under a nitrogen stream to obtain the target polymer. The melting point of the obtained polymer was 336°C, and the melt viscosity at 350°C was 19.0 Pa·s. The melt viscosity of the above polymer was measured in the same manner as the melt viscosity measurement method described below. 4-Hydroxybenzoic acid (HBA); 1380g (60 mol%) 2-Hydroxy-6-naphthoic acid (HNA); 157 g (5 mol%) 1,4-Phenylenedicarboxylic acid (TA): 484 g (17.5 mol%) 4,4'-Dihydroxybiphenyl (BP); 388 g (12.5 mol%) N-acetyl-p-aminophenol (APAP); 126 g (5 mol%) Metal catalyst (potassium acetate catalyst); 110mg Acylating agent (acetic anhydride); 1659g
[0052] Liquid crystal polyester resin (LCP2)
[0053] After the following raw materials were charged into the polymerization vessel, the temperature of the reaction system was raised to 140°C and reacted at 140°C for 1 hour. After that, the temperature was further raised to 360°C over 5.5 hours, and the pressure was reduced to 5 Torr (i.e., 667 Pa) over 20 minutes, and melt polymerization was carried out while distilling off acetic acid, excess acetic anhydride, and other low boiling points. After the stirring torque reached a predetermined value, nitrogen was introduced to change from a reduced pressure state to a normal pressure state and then to a pressurized state, and the polymer was discharged from the bottom of the polymerization vessel, and the strands were pelletized to obtain the target polymer as pellets. The melting point of the obtained polymer was 355°C and the melt viscosity was 10 Pa·s. The melt viscosity of the above polymer was measured in the same manner as the melt viscosity measurement method described below. 4-Hydroxybenzoic acid (HBA); 1040g (48 mol%) 6-Hydroxy-2-naphthoic acid (HNA); 89 g (3 mol%) 1,4-Phenylenedicarboxylic acid (TA): 547 g (21 mol%) 1,3-Phenylenedicarboxylic acid (IA); 91 g (3.5 mol%) 4,4'-Dihydroxybiphenyl (BP); 716 g (24.5 mol%) Potassium acetate catalyst: 110mg Acetic anhydride: 1644g
[0054] <Materials other than liquid crystal resin> Fibrous conductive filler: HTC432 (Teijin Limited, PAN-based carbon fiber, chopped strand, fiber diameter 7 μm, length 6 mm) Carbon black: VULCAN XC305 (Cabot Japan Co., Ltd., median diameter 20 nm, proportion of particles with a particle diameter of 50 μm or more is 20 ppm or less) Talc: Crown Talc PP (Matsumura Sangyo Co., Ltd., talc, median diameter 14.6 μm) Mica: AB-25S (Made by Yamaguchi Mica Co., Ltd., mica, median diameter 25.0 μm) Silica: Denka fused silica FB-5SDC (manufactured by Denka Co., Ltd., silica, median diameter 4.0 μm) Glass fiber: ECS03T-786H (Nippon Electric Glass Co., Ltd., chopped strand, fiber diameter 10 μm, length 3 mm)
[0055] <Production of Liquid Crystalline Resin Composition> The above components were melt-kneaded in the ratios (unit: mass %) shown in Tables 1 to 3 at the cylinder temperatures shown below using a twin-screw extruder (TEX30α manufactured by The Japan Steel Works, Ltd.) to obtain liquid crystal resin composition pellets. Cylinder Temperature: 350°C (other than Example 23) 370°C (Example 23)
[0056] <Melt viscosity> Using a Capillograph 1B model manufactured by Toyo Seiki Seisakusho Co., Ltd., the melt viscosity of the liquid crystal resin composition was measured at a temperature 10 to 20°C higher than the melting point of the liquid crystal resin, using an orifice with an inner diameter of 1 mm and a length of 20 mm, at a shear rate of 1000 / sec in accordance with ISO11443. The measurement temperature was 350°C except for Example 23, and 370°C for Example 23. The results are shown in Tables 1 to 3.
[0057] <Volume resistivity> The pellets of the examples and comparative examples were molded under the following molding conditions using a molding machine ("SE100DU" manufactured by Sumitomo Heavy Industries, Ltd.) to obtain a flat test piece 1 of 80 mm x 80 mm x 1 mmt or a flat test piece 2 of 80 mm x 80 mm x 2 mmt. The flat test piece 1 was used to measure the volume resistivity (hereinafter also referred to as "1 mmt volume resistivity") in accordance with JIS K 7194 using a resistivity meter ("Loresta-GP" manufactured by Nitto Seiko Analytech Co., Ltd.). In addition, the flat test piece 2 was used to measure the volume resistivity (hereinafter also referred to as "2 mmt volume resistivity") in accordance with JIS K 7194 using a resistivity meter ("Loresta-GP" manufactured by Nitto Seiko Analytech Co., Ltd.). Furthermore, the difference between the 1 mmt volume resistivity and the 2 mmt volume resistivity was calculated. The results are shown in Tables 1 to 3. When the absolute value of the above difference was 0.10 Ω·cm or less, it was evaluated that the variation in volume resistivity was particularly small, regardless of thickness. [Molding conditions] Cylinder Temperature: 350°C (other than Example 23) 370°C (Example 23) Mold temperature: 80℃ Injection speed: 33mm / sec
[0058] <Electromagnetic wave shielding> The pellets of the examples and comparative examples were molded under the following molding conditions using a molding machine ("ES3000" manufactured by Nissei Plastic Industrial Co., Ltd.) to obtain test pieces of 120 mm x 120 mm x 2 mmt. The electromagnetic shielding properties of these test pieces at a frequency of 100 MHz were measured by the KEC method. The results are shown in Tables 1 to 3. [Molding conditions] Cylinder Temperature: 350°C (other than Example 23) 370°C (Example 23) Mold temperature: 80℃ Injection speed: 100mm / sec
[0059] [Table 1]
[0060] [Table 2]
[0061] [Table 3]
[0062] As is clear from the results shown in Tables 1 to 3, the compositions of the examples were confirmed to have low melt viscosity and high fluidity, and therefore excellent moldability, and the molded articles obtained from the compositions of the examples were confirmed to have excellent electromagnetic wave shielding properties.
Claims
1. An electromagnetic wave shielding member comprising a molded product of a liquid crystalline resin composition containing (A) a liquid crystalline resin, (B) a fibrous conductive filler, and (C) a granular conductive filler, The liquid crystal resin (A) is an aromatic polyester or an aromatic polyester amide having a structural unit derived from an aromatic hydroxycarboxylic acid as a structural component, The total content of the (B) fibrous conductive filler and the (C) granular conductive filler is 15 to 60 mass %, the mass ratio of the content of the fibrous conductive filler (B) to the content of the granular conductive filler (C) is 0.40 to 21.0; The (B) fibrous conductive filler is a carbon fiber, The particulate conductive filler (C) is carbon black, the difference between the 1 mmt volume resistivity and the 2 mmt volume resistivity of the electromagnetic wave shielding member is −0.52 to 2.08 Ω cm; The electromagnetic shielding member has an electromagnetic shielding property of 35 dB or more at a frequency of 100 MHz, as measured in accordance with the KEC method.
2. The total content of the (B) fibrous conductive filler and the (C) granular conductive filler is 20 to 50 mass %, 2. The electromagnetic shielding material according to claim 1, wherein the mass ratio of the content of the fibrous conductive filler (B) to the content of the granular conductive filler (C) is 0.50 to 20.
0.
3. The electromagnetic wave shielding member according to claim 1 , wherein the liquid crystalline resin composition further contains (D) a non-conductive filler.
4. 4. The electromagnetic shielding material according to claim 3, wherein the content of the non-conductive filler (D) is 2 to 8 mass %.
5. 4. The electromagnetic shielding member according to claim 3, wherein the non-conductive filler (D) is at least one selected from the group consisting of talc, mica, glass flakes, silica, glass beads, glass balloons, potassium titanate whiskers, calcium silicate whiskers, milled glass fibers, and glass fibers.
6. 4. The electromagnetic shielding material according to claim 3, wherein the non-conductive filler (D) is at least one selected from the group consisting of talc, mica, silica, and glass fiber.
Citation Information
Patent Citations
Molding method of composite molding
JP2000225628A
Highly electroconductive resin molded article
JP2004035826A
Liquid crystal polyester resin composition and electromagnetic wave shielding member
JP2008111010A
Liquid crystalline polymer composition and molded article
JP2010095669A
Thermoplastic resin composition having electromagnetic interference shielding properties
JP2010526888A